One chance in a million: altruism and the bone marrow registry - Ted Bergstrom; Rod Garratt; Damien Sheehan-Connor (Center for Economic Studies and ifo Institute (CESifo), 2007)
Transplants of donated stem cells save the lives of many patients with blood diseases. Donation is somewhat painful, but rarely has lasting adverse effects. Patients can accept transplants only from donors with compatible immune systems. Those lacking a sibling match must seek donations from the population at large. The probability that two persons of the same race are compatible is less than 1/10,000. Health authorities maintain a registry of several million genetically-tested potential donors who have agreed to donate if asked. We study the peculiar structure of voluntary public good provision represented by the registry, and compare the marginal benefits and marginal costs of expanding the registry.
Keywords: D64; H51; 330; Organtransplantation; Gentechnik; Altruismus; Kosten-Nutzen-Analyse; USA